Evaluation of Effects of Harvest on Alligator Populations in Louisiana. Issue 4 (16th March 2021) - Joanen, Ted; Merchant, Mark; Griffith, Rebekah; Linscombe, Jeb; Guidry, Angela
ABSTRACT: Biologists with the Louisiana Department of Wildlife and Fisheries, Louisiana, USA, have managed statewide annual harvest of alligators ( Alligator mississippiensis ) for 35 years (1981–present). We collected and analyzed harvest data for Louisiana alligators to determine the effects of harvest on the population structure, focusing on the larger size classes (≥274 cm) of this slow‐growing species. Linear regression analyses revealed that body size‐class structure, based on overall average size and the percentage of animals harvested in the larger size classes was relatively stable. Annual aerial alligator nest counts indicated a continual growth of the population, and over time harvested alligators maintained a constant average size. Analyses of population size (based on number of nests and population modeling) indicated that the current annual harvest represents approximately 3% of the population. Linear regression analysis showed that annual hunter success declined only slightly during the study period, and the scheduling of the hunt season after the hatch period and recommended hunting in areas not frequented by breeding females provides economic opportunities for hunters to participate in a sustainable harvest that preserves the larger size classes of alligators in the population. Strict enforcement of existing laws was a key factor responsible for the success of this harvest program. Comparison of alligator population size and number of harvest‐related citations indicated that illegal harvest did not have a negative effect on population size, and linear regression analyses revealed that the rate of increase in citations was lower than the increase in populations over the study period. The results of this harvest program indicated that alligators can be hunted in a sustainable manner if hunting is conducted after the hatch period and occurs in areas that primarily exclude the harvest of adult females, and strict law enforcement curbs illegal activities that negatively affect populations. © 2021 The Authors. The Journal of Wildlife Management published by Wiley Periodicals LLC on behalf of The Wildlife Society. Abstract : Analysis of data collected from a 31‐year (1985–2015) statewide harvest of alligators in Louisiana showed that the total population increased and the population structure remained stable. Because of intensive regulation of harvest and habitat conservation, the Louisiana Department of Wildlife and Fisheries has managed a sustainable harvest of alligators, which has included the harvest of almost 900, 000 animals. Results indicated that recruitment into larger size classes was greater than hunting mortality during the study period.